Understanding Geography Learning Achievement: The Role of Parental Attention and Physical Learning Environment among High School Students - Claire Chambers; Antonia Ria Issaura; Mousumi Boral; Aeshah Mujahid; Ghufran Jafar Ismail (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to examine the relationships between parental attention, the physical learning environment, and Geography learning achievement among high school students. It also aims to determine the combined contribution of parental attention and the physical learning environment to students’ Geography learning achievement. Methodology: Quantitative correlational research design; survey method; structured questionnaire; documentation of Geography achievement scores; proportional random sampling; 105 high school students as respondents; Likert-scale instrument; Kolmogorov–Smirnov normality test; linearity test; multicollinearity test; Pearson product-moment correlation; multiple linear regression; SPSS statistical software. Main Findings: Parental attention was positively associated with Geography learning achievement (r = 0.425, p < 0.001). The physical learning environment was positively associated with Geography learning achievement (r = 0.466, p < 0.001). Together, parental attention and the physical learning environment significantly predicted Geography learning achievement (R = 0.574, R² = 0.330, p < 0.001). Parental attention contributed more strongly than the physical learning environment. Novelty/Originality of this study: This study integrates parental attention and the physical learning environment within a Geography education framework and evaluates their individual and combined contributions to learning achievement. Unlike previous studies that focused on general academic performance, this research specifically examines Geography learning achievement, providing empirical evidence on how family support and home learning conditions jointly influence student outcomes.